CEOs’ leadership behaviors and new venture team stability: The effects of knowledge hiding and team collectivism - Ma, Hongjia; Tang, Sisi; Zhao, Changyi (Frontiers in Psychology, 2022)
The reasons for new venture team instability gradually have become a vital issue in the entrepreneurship literature. While chief executive officers’ (CEOs) leadership behaviors are regarded as a critical element of governance within new venture teams, few studies explored the role played by CEOs’ leadership behaviors in new venture team stability. Drawing on the transactional-transformational leadership model, this study divides CEOs’ leadership behaviors in new ventures into two categories, namely, transformational and transactional leadership behaviors. Based on the social exchange theory and the social information processing theory, this study constructs a moderating mediation model to understand how transformational and transactional leadership affects new venture team stability. In this model, knowledge hiding is used as mediating role and team collectivism is used as moderating role. A test of the proposed theoretical model, among 66 new venture teams in China, reveals that (1) transformational leadership and transactional leadership are positively related to new venture team stability. (2) Knowledge hiding mediates the association between transformational leadership and new venture team stability and that between transactional leadership and new venture team stability. (3) A high level of team collectivism corresponds to a stronger relationship between transformational leadership and knowledge hiding and a greater indirect effect of transformational leadership on new venture team stability through knowledge hiding. Theoretically, this study explores the mechanisms and boundary conditions of the effect of transformational leadership, transactional leadership, and new venture team stability, which is an enrichment to the study of governance within new venture teams. It enlightens managers to take effective measures to reduce knowledge hiding and maintain team stability in new venture teams.